Management of Dynamic Archives for Education Personnel in State Madrasah Aliyah - Hanifah, Fitri; Setyaningsih, Rini (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2023)
This research aimed at knowing 1) creating dynamic archives in the administrative section, and 2) storing dynamic archives in the administrative section at State Islamic Senior High School 3 Pekanbaru.  It was a qualitative research with a descriptive method.  The subjects of this research were the head of administration, administrative staff as key informants, and the vice of student affairs and teachers as additional informants.  The object of this research was the management of archives in the administration section at State Islamic Senior High School 3 Pekanbaru.  Interview, observation, and documentation techniques were used for collecting the data.  The data were analyzed by using reduction, presentation, and conclusion. The results of this research show that: 1) The creation of dynamic archives in the administration section of MAN 3 Pekanbaru was carried out well, including the process of incoming and outgoing letters. 2) The storage of dynamic archives in the administration section of MAN 3 Pekanbaru was carried out well, however, there were a few obstacles in the archive retrieval process, namely archives or letters that have been disposed of and are located outside the administration room, such as the principal's room, the deputy principal's room for student affairs and curriculum, forgetting to take them back, so there are archives that are not stored in the filing cabinet.